Perencanaan Instalasi Pengolahan Air Limbah Domestik di PT. X - Dinda Dwi Paramita; Etih Hartati (Jurnal Serambi Engineering, 2024)
PT X is a pulp production company. The company will be located in the province of North Kalimantan and will employ 1220 people. The activities of these employees will generate liquid waste that will pollute the receiving water body and harm human health if the liquid waste is not treated before being discharged into the environment. Therefore, in this design, a Domestic Wastewater Treatment Plant (DWWTP) design is carried out so that the liquid waste can be treated to meet the quality standards based on the Minister of Environment and Forestry Regulation No. 68 of 2016. The method used in this planning is the desk study method, with the planning stages being the calculation of domestic wastewater discharge, the analysis of domestic wastewater quality, the determination of biological unit technology using the Weighted Ranking Technique method, the calculation of the dimensions of each treatment unit, and the drawing of the DWWTP scheme. Based on the calculation results, the maximum domestic wastewater discharge at PT X is 48 m3/day. The alternative biological units compared were the complete mix activated sludge (CMAS) unit, the trickling filter and the moving bed bioreactor (MBBR). The selected series of treatment units are grease trap, basket strainer, clarifier I, CMAS, clarifier II and disinfection tank.